The SAGE encyclopedia of classroom management - Scarlett, W. George (SAGE Publications, 2015)
A teacher's ability to manage the classroom strongly influences the quality of teaching and learning that can be accomplished. Among the most pressing concerns for inexperienced teachers is classroom management, a concern of equal importance to the general public in light of behaviour problems and breakdowns in discipline that grab newspaper headlines. But classroom management is not just about problems and what to do when things go wrong and chaos erupts. It's about how to run a classroom so as to elicit the best from even the most courteous group of students. An array of skills is needed to produce such a learning environment
Keywords: Classroom management -- Encyclopedias; Unterrichtsdisziplin; Schüler; Unterrichtsorganisation; Aufsatzsammlung